Training guide : administering windows server 2012 - Thomas, Orin (O'Reilly Media, Inc. CaliforniaUS, 2013)
Describes what an administer of the Windows Server 2012 operating system with several years of on-the-job experience does and understands. Covers the majority of the topics and skills that are the subject of the Microsoft certification exam 70-411.